Исследование работы пластинчатой греющей камеры с кипением в каналах - Фокин, Виталий Сергеевич; Данилов, Д. Ю.; Шульгин, Юрий Витальевич (НТУ "ХПИ", 2009)
The results of research of work of channels broad plates warming camers with boiling of solution in channels are resulted in the article. Influencing of parameter of evaporation of тер of relation of areas of section of reverse circulation pipe and channels is shown a boiling process on intensity of carry heat flows in which. It is marked that channels broad warming camers at the observance of the recommended correlations of contour of circulation have more high values of coefficient of heat emission than tubular.
Keywords: теплопередача; поверхность нагрева; греющая камера; движение пара; пластина